HOW TO IMPROVE ONLINE SHOP CUSTOMER SATISFACTION THROUGH SERVICE QUALITY - Maghfur, M; Hurriyati, Ratih; Adieb Sultan, Moch. (Dinasti Publisher, 2021)
This study aimed to figure out the Effect of Quality System, E-Service Quality, and Information Quality on Value Perception and Customer Satisfaction of an online marketplace. The number of samples used was 110 respondents who have become customers at Bukalapak, a well-known online shop in Indonesia. Data were collected through a survey toward the customers. The PLS-SEM was applied to evaluate the relationship among variables. The results indicated that the E-Service Quality Variable, Quality System, and also Information Quality positively and significantly affected the Customer Satisfaction Variable. However, only Quality System and Information Quality positively and significantly affected Value Perception, showing its mediation role to Customer Satisfaction. This study suggests that online marketplaces should have more concern to their Quality System and Information Quality as well as E-service quality to improve their sales performance by increasing their customer satisfaction and Value Perception.